2017
DOI: 10.14295/cs.v7i4.1671
|View full text |Cite
|
Sign up to set email alerts
|

Irrigação com águas salinas e aplicação de prolina foliar em cultivo de pimentão ‘All Big’

Abstract: It is proposed in this study the evaluation of the growth and yield of ‘All Big’ sweet pepper under foliar application of proline and irrigation with saline water. The research was conducted in pots adapted as drainage lisimeters under greenhouse conditions, using an Eutrophic Entisol with sandy-loam texture in the municipality of Campina Grande, PB, Brazil. A randomized block design was used testing two levels of electrical conductivity of irrigation water - ECw (0.6 and 3.0 dS m-1) associated to four proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 8 publications
2
38
0
1
Order By: Relevance
“…These results agreed with those reported by various authors who studied the bell pepper crop under saline stress conditions, cultivated in either soil (Leonardo et al, 2007;Lima et al, 2016) or substrate (Arruda et al, 2011;Rubio et al, 2011;Nunes et al, 2013;Furtado et al, 2017;Lima et al, 2017). Reductions in fruit size and weight due to saline stress and, consequently, in the economic performance of the crop, are caused by physiological and biochemical changes in the cells or at the molecular level (Munns & Tester, 2008).…”
Section: F1 F2 F3 F4 F5supporting
confidence: 90%
See 1 more Smart Citation
“…These results agreed with those reported by various authors who studied the bell pepper crop under saline stress conditions, cultivated in either soil (Leonardo et al, 2007;Lima et al, 2016) or substrate (Arruda et al, 2011;Rubio et al, 2011;Nunes et al, 2013;Furtado et al, 2017;Lima et al, 2017). Reductions in fruit size and weight due to saline stress and, consequently, in the economic performance of the crop, are caused by physiological and biochemical changes in the cells or at the molecular level (Munns & Tester, 2008).…”
Section: F1 F2 F3 F4 F5supporting
confidence: 90%
“…The first one was the high number of fruits with blossom-end rot, especially in treatments F1 and F2, a typical symptom of Ca deficiency in the fruits resulting from high Na + concentration, which was previously reported by various authors (Arruda et al, 2011;Nunes et al, 2013;Rubio et al, 2009). The second reason was the occurrence of small fruits in plants fertigated with nutrient solutions of higher salinity, confirming the results observed by other authors (Lima et al, 2016;Furtado et al, 2017).…”
Section: F1 F2 F3 F4 F5supporting
confidence: 87%
“…Proline concentrations were determined based on the work of Lima et al (2016), who observed higher growth of bell pepper plants cv. 'All Big' subjected to saline stress when proline concentration of 12.17 mM was used.…”
Section: Experiments Localization and Treatmentsmentioning
confidence: 99%
“…These processes include translocation of carbohydrates to sink tissues, and in the diversion of sources of energy to other processes, such as osmotic adjustment, synthesis of compatible solutes, repair of damage caused by salinity, and maintenance of basic metabolic processes (Lucena, Siqueira, Martinez, & Cecon, 2012). In the bell peppers, G. S. Lima et al (2016) found that the increase in ECw from 0.6 to 3.0 dS m -1 resulted in a marked reduction in the growth in stem diameter, at 90 days after transplanting.…”
Section: Resultsmentioning
confidence: 99%